The KEGIATAN PELATIHAN PENGEMBANGAN APLIKASI MOBILE - Setiawan, Renanda; Rizki, Fahlul (Jurnal Rekayasa Perangkat Lunak, 2025)
The advancement of digital technology has intensified the need for information technology skills among students, particularly in mobile application development. A training program held at SMK Negeri 1 Bandung in May 2024 served as a concrete initiative to bridge the gap between industry demands and student competencies. This study aims to describe the training process, instructional methods, and its impact on participants. A descriptive qualitative approach with a case study design was applied. Data were collected through direct observation during the training, interviews with 20 students, and documentation of final projects. The training covered material on Android Studio, Kotlin programming, UI/UX design, and Firebase integration. Findings revealed that the use of learning by doing and project-based learning methods effectively enhanced students’ technical skills and creativity. Participants successfully developed prototype applications such as local product catalogs, food ordering systems, and school task managers. Additionally, the training increased students' interest in pursuing careers in information technology. Strong institutional support and experienced facilitators were key success factors. In conclusion, mobile application development training positively contributes to strengthening students’ digital competencies. It is recommended that similar programs be conducted regularly, with expanded collaboration between schools and local tech industries to ensure the applicability and market relevance of training outcomes.